John Fiske's Semiotic Analysis: Representation of Social Criticism in Pretty Boys - Tasya Arlina; Reni Nuraeni (Budapest International Research and Critics University, 2022)
This study aims to analyze the representation of social criticism in the film Pretty Boys using John Fiske's semiotic analysis. In this study, the researcher used a qualitative research method with a descriptive type of research to examine a social critique that occurred in the film